Position Law Letter Circular No. 13 Year 2021 About the Cancel of Homecoming for Eid Al-Fitr in 1441 Hijriah and Efforts to Control the Spread of Corona Viruses Disease (Covid-19) During the Holy Month of Ramadan 1442 Hijriah - Maharani Nur Azizah; Hananto Widodo; Muhammad Fajar Adiantama (NOVUM : JURNAL HUKUM, 2024)
The 2021 Homecoming Circular Letter was issued to regulate public mobility during the Eid homecoming period as part of the government’s effort to control the spread of COVID-19. As an instrument created under urgent circumstances, the Circular Letter reflects the implementation of freies ermessen, allowing authorized officials to exercise discretion. This study aims to analyze the legal position and implications of the 2021 Homecoming Circular Letter, especially in relation to the principles of discretionary authority and statutory hierarchy. The research is normative in nature, using a statutory and conceptual approach. Legal materials were obtained through literature study and analyzed prescriptively to evaluate the consistency of the Circular Letter with existing legal norms. The findings show that Circular Letters are not explicitly included in Law Number 12 of 2011 concerning the Formation of Laws and Regulations. However, they may still carry binding power if supported by higher legal instruments such as Government Regulation No. 21 of 2020 and Presidential Decree No. 11 of 2020. Substantively, the 2021 Circular Letter aligns with Law No. 6 of 2018 on Health Quarantine. The authority of the COVID-19 Task Force to issue the Circular is justified in the context of pandemic-related emergency response. The study recommends that the issuance of Circular Letters must not contradict the hierarchy of laws and should emphasize public benefit, clarity, and legal certainty, particularly in times of crisis when government discretion is exercised.